NON-LINIER COMPRESSION STRESS-STRAIN CURVE MODEL FOR HARDWOOD - Adhijoso Tjondro; Bambang Suryoatmono; Iswandi Imran (MEKANIKA, 2016)
Non-linier compression stress-strain relationship was derived from experimental investigation of 144 small clear specimens of three Indonesian hardwood species, namely Acacia, Meranti and Kruing. Both compression parallel to the grain and compression perpendicular to the grain were tested. The stress-strain curve consists of linier-elastic line until proportional limit and bi-linier curve. Stress-strain curve parameters for compression parallel to the grain, such as elastic modulus, post-elastic modulus, proportional limit, ultimate stress and post-elastic strain limit were derived based on the specific gravity. And also stress-strain curve parameters for compression perpendicular to the grain, such as elastic modulus, post-elastic modulus and proportional limit were derived based on the specific gravity and the angle between stress direction and tangential axis direction. Compression strength perpendicular to the grain in tangential direction was found much lower than compression strength perpendicular to the grain in radial direction.